2017
DOI: 10.4314/ahs.v17i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Renal histoarchitectural changes in nevirapine therapy: possible role of kolaviron and vitamin C in an experimental animal model

Abstract: Background: There is paucity of literature regarding the nephrotoxicity of antiretroviral drugs and its interaction with plantbased adjuvants. This study investigates the attenuating effect of kolaviron in nevirapine-therapy on the histological structure of the kidneys of adult male Sprague-Dawley rats. Objective: To determine the attenuating influence of anti-oxidant status of kolaviron on the kidneys of experimental animals following nevirapine administration. Methods: Forty eight pathogen-free adult male Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These reports retrieved in the literature search demonstrate the uses of vitamin C to prevent and treat AKI before and after the establishment of renal injury model, respectively. Blood creatinine, urea, malondialdehyde, and reduced glutathione levels, the makers of renal functions and oxidative stresses, were measured in these studies [ 42 , 43 , 44 , 45 ]. The results showed that vitamin C protected the kidneys from injuries caused by external factors, and also facilitated repair after damage occurred.…”
Section: Vitamin C and Its Potential For The Protection Of Renal Injury In Patients With Covid-19mentioning
confidence: 99%
“…These reports retrieved in the literature search demonstrate the uses of vitamin C to prevent and treat AKI before and after the establishment of renal injury model, respectively. Blood creatinine, urea, malondialdehyde, and reduced glutathione levels, the makers of renal functions and oxidative stresses, were measured in these studies [ 42 , 43 , 44 , 45 ]. The results showed that vitamin C protected the kidneys from injuries caused by external factors, and also facilitated repair after damage occurred.…”
Section: Vitamin C and Its Potential For The Protection Of Renal Injury In Patients With Covid-19mentioning
confidence: 99%
“…Farombi et al ( 2009 ) also suggested that its effect may be achieved through inhibition of cyclooxygenase (COX) and inducible nitric oxide synthase (iNOS) expression. Similarly, KV was also tested in the scenario of renal (Adaramoye 2009 ; Adedara et al 2015 ; Offor et al 2017 ; Alabi et al 2018 ) and gastro-intestinal (Olaleye and Farombi 2006 ; Onasanwo et al 2011 ; Akinrinde et al 2015 ) protection in animal models against similar toxic agents as in the case of liver toxicity tests. Both nephroprotective and gastro-protective effect is presumably exerted via similar mode of action.…”
Section: Resultsmentioning
confidence: 99%
“…20 Similarly, Nigerian reseachers report on the renal histo-architectural changes in nevirapine therapy and the possible role of kolaviron and vitamin C in an experimental animal model. 21 Khat use is a big challenge in the Horn of Africa. From Ethiopia, we have a paper on the prevalence of khat chewing and its effect on academic performance in Sidama zone, Southern Ethiopia 22 A must read.…”
Section: 11mentioning
confidence: 99%